Ricky Ricotta's mighty robot vs. the mecha-monkeys from Mars - Pilkey, Dav, 1966-; Santat, Dan (New York, NY : Scholastic Inc., 2014)
A small mouse and his best friend, a giant flying robot, attempt to save the Earth when an evil Martian monkey and his mechanical creations attack.
"4"--Spine.
Originally published in 2002 in a slightly different form by Blue Sky Press.
3.6
K-3
K-3
3.6.
Keywords: Ricotta, Ricky (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Robots -- Juvenile fiction; Heroes -- Juvenile fiction; Monkeys -- Juvenile fiction; Ricotta, Ricky (Fictitious character) -- Fiction; Mice -- Fiction; Robots -- Fiction; Heroes -- Fiction; Monkeys -- Fiction; Humorous stories; Ricotta, Ricky (Fictional character) -- Fiction; Mice -- Fiction; Robots -- Fiction; Heroes and heroines -- Fiction; Monkeys -- Fiction; Humorous fiction; Mars (Planet) -- Juvenile fiction; Mars (Planet) -- Fiction; Mars (Planet) -- Fiction